The impact of environmental factors on the occurrence of congenital heart disease in the form of hypoplastic left heart syndrome - Gładki, Marcin Michał; Składzień, Tomasz; Skalski, Janusz Hieronim (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Congenital heart defects are the most common abnormalities in neonatal age. Congenital heart defects occur with a frequency of 3-12/1000 births. A special group is constituted by children with hypoplastic left heart syndrome because their treatment is extremely complex, requiring three-stage surgery and the involvement of various specialists. Material and methods: We analysed 100 infants with congenital heart defects in the form of hypoplastic left heart syndrome (HLHS). They were compared with a control group of 100 newborns without structural heart defects. The children’s parents were asked to fill out a questionnaire consisting of 10 simple questions. It had been constructed in consultation with a psychologist in order not to offend the feelings of the parents affected by the illness of their offspring. Results: Congenital heart defects were present in the family medical histories of 16 HLHS children and 11 healthy children (p = 0.4). Genetic disorders were present in the family medical histories of 13 HLHS children and 15 healthy children (p = 0.73). In the HLHS group, the mothers smoked cigarettes or were exposed to tobacco smoke in 32% of cases; in the control group, this proportion amounted to 23% (p = 0.76). Conclusions: The study found no relationship between the occurrence of hypoplastic left heart syndrome in children and the parents’ age, the presence of genetic disorders, or heart defects in the family medical histories.